Effect of combined application of poultry manure and inorganic fertiliser on yield and yield components of maize intercropped with soybean - Gezahegn, Almaz Meseret; Abd Halim, Mohd Ridzwan; Mohammad Yusoff, Martini (Universiti Putra Malaysia Press, 2017)
A field experiment was conducted to evaluate the effect of the combined application of poultry manure and inorganic fertiliser on yield and the yield component of maize (Zea mays L) and soybean (Glycine max L. Merril) intercrops. Treatments comprised combinations of three intercropping systems (sole maize, sole soybean and maize+soybean) and four nutrient management practices [control, 100% NPK, 100% poultry manure (PM) and 50 % NPK+50% PM]. The experiment was laid out in a randomised complete block design (RCBD) with three replications. The results revealed that intercropping of maize with soybean significantly reduced soybean yield and yield components, but maize yield and yield traits were not significantly affected by intercropping. Land Equivalent Ratio (LER) was >1, indicating a beneficial effect of intercropping soybean with maize. For both maize and soybean, there were no significant differences in yield between application of 100% NPK and the 50% NPK+50% PM fertiliser. A combined application of 50% NPK and 50% PM gave the highest monetary advantage in intercropping system. It can be concluded that a 50% substitution of inorganic fertiliser with poultry manure is recommended to reduce use of chemical fertilisers without sacrificing crop yield.